Losing Mum and Pup a memoir - Buckley, Christopher 1952- (Twelve, 2009)
Bestselling author Buckley's most personal and transcendent work--the tragicomic true story of the year in which he lost both of his parents. The author offers consolation, wit, and warmth to those coping with the death of a mother or father.
Includes index.
Keywords: Buckley, Christopher -- 1952- -- Family; Buckley, William F -- (William Frank) -- 1925-2008 -- Last years; Buckley, William F -- (William Frank) -- 1925-2008 -- Death and burial; Buckley, Christopher -- 1952-; Buckley, William F. -- 1925-2008; Geschichte 1900-2000; Psychologie; Authors, American -- 20th century -- Family relationships; Parents -- Death -- Psychological aspects; Eltern; Autobiografie